Regular Exercise and Depressive Symptoms in Community-Dwelling Elders in Northern Taiwan. Issue 4 (December 2016) - Chang, Shu-Hung; Chien, Nai-Hui; Chen, Miao-Chuan
ABSTRACT: Background: According to World Health Organization, depressive disorder will be a Top 2 disease in the world by 2020. In light of Taiwan's rapidly increasing elderly population, elderly psychological health is expected to become an increasingly important issue in healthcare. Purpose: This study examines the association between regular exercise and depressive symptoms in community-dwelling older adults by gender in northern Taiwan. Methods: The participants were selected using a probability-proportional-to-size procedure from community-dwelling adults who were aged 65 years or older and living in northern Taiwan. A cross-sectional study and interviews were used to collect information about their exercise behaviors, depressive symptoms, and the factors influencing the depressive symptoms. Percentage, chi-square, t test, and logistic regression were used to analyze the data. Result: One thousand twenty elderly individuals completed the questionnaires. Among the participants with the average age of 73.5 years, 44.5% were men, and 55.5% were women. Two hundred seventeen of the participants (21.3%) had depressive symptoms. Five hundred eighty-five of the participants (57.4%) exercised regularly. The result of logistic regression showed that regular exercise was a significant predictor of depressive symptoms in elderly individuals (odds ratio = 3.54, 95% confidence interval [1.76, 7.12]). Other factors such as gender, chronicle diseases, and health status were not related to depressive symptoms. Moreover, both for male and female individuals, regular exercise was a significant predictor of depressive symptoms (odds ratio = 4.76, 95% confidence interval [1.65, 13.72] and odds ratio = 3.03, 95% confidence interval [1.18, 7.69], respectively). Other factors were not related to depressive symptoms. Conclusions/Implications for Practice: This study shows regular exercise to be a significant predictor of depressive symptoms in both men and women. Therefore, senior citizens should be encouragedto exercise regularly as a way to promote good mental health.